Some Remarks on the Musical Lexicon of Dante’s Commedia - Calvia, Antonio (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
This essay examines four verbs from Dante’s Commedia that relate to music. Sections 2 and 3 discuss alleluiando and osannar, respectively. Section 4 considers the verb inneggiar—regarded, until Giorgio Inglese’s 2021 edition, as a corrupt reading of inveggiar—and argues that its similarity to the previously discussed denominal verbs, alleluiare and osannare, further supports inneggiar as the original lectio. Section 5 explores the meaning of alternando, a term with distinct, if not immediately obvious, musical resonance. As an introduction to the subject matter, section 1 provides an overview of the Commedia’s musical lexicon.